Extraction, characterization, and anticancer potential of extracellular polymeric substances from marine actinobacteria of Streptomyces species - Z Mohamed Noufal; Pitchiah Sivaperumal; P Elumalai (Wolters Kluwer Medknow Publications, 2022)
To check the ability of the anticancer activity, the extracted extracellular polymeric substances (EPS) from marine actinobacteria were done. Potential of the anticancer activity of EPS which was extracted from marine actinobacteria of Streptomyces species through an assay called MTT. Marine actinobacterial isolation, identification and micromorphology of the strain, and biochemical analysis were performed (Shirling and Gottlieb, 1966). The production of EPS from marine actinobacteria was quantified(P. Sivaperumal et al., 2018). Carbohydrate content in the EPS was quantified, and MCF-7 cell proliferation was done using an MTT assay. EPS-producing marine Streptomyces was isolated and identified. The production of EPS and their protein, carbohydrate, lipid, and other parameters were estimated. Further, the EPS showed more than 50% of inhibition after 72 h using the MTT assay in the MCF-7 cancer cell line. The present study exhibited that EPS from marine Streptomyces species has significant anticancer activity.